PENGARUH DAYA TARIK BRAND AMBASSADOR DAN INTENSITAS KOMUNIKASI ELECTRONIC WORD OF MOUTH TERHADAP MINAT BERTRANSAKSI DI LAZADA - Septiana Hadiwinoto, Jessica; Ratri Rahmiaji, Lintang; Pradekso, Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The phenomenon of online shopping is now increasingly widespread and much in demand by the public. Various e-commerce are present in Indonesia and compete to be number one. In addition, the Hallyu/Korean Wave phenomenon emerged which made ecommerce attract brand ambassadors from South Korea to represent their brand. Lazada as one of the e-commerce sites in Indonesia also applies this strategy, for the first time Lazada uses a brand ambassador which is expected to increase interest in transacting on Lazada. In addition, data shows that 24% of the public get information about e-commerce through word of mouth communication, which at this time can also occur through internet intermediaries or called electronic word of mouth. This study aims to determine the effect of brand ambassador attractiveness and the intensity of electronic word of mouth communication on interest in transacting at Lazada. The theory used in this research is Source Attractiveness theory and Buyer Information Environment theory. The test is done by simple regression test with nonprobability sampling technique. The sample used was 50 people aged 18-25 years, knowing Lazada's brand ambassadors, had talked about Lazada online. The results showed that the attractiveness of the brand ambassador (X1) on the interest in transacting at Lazada (Y) had a significance value of 0.025 which means that it shows effect. Then, the intensity of electronic word of mouth (X2) communication on interest in transacting at Lazada (Y) has a significance value of 0.006 which means it also shows an effect